STOCK MARKET FLUCTUATİONS, MACROECONOMİC INDİCATORS, AND INVESTOR SENSİTİVİTY: THE CASE OF TURKEY (Third Sector Social Economic Review, 2024)
The aim of this study is to examine the relationship between price fluctuations in stock markets, macroeconomic indicators and investor sentiment for the period 12.2005-09.2023. For this purpose, two different models were established in the study and analyzed with the ARDL Bounds Test Approach. According to the findings obtained from the analysis of the first model, a change in interest rates in the long term creates a negative effect on the BIST100 index, while the increase in the industrial production index and M2 money supply affects the BIST100 index positively. Again, when we look at the short-term coefficients estimated for the first model, a negative relationship was detected between the exchange rate and the three-period lagged value of the exchange rate and the BIST100 index, at a statistically significant level of 1%. On the other hand, the difference between CPI and BIST100 index is statistically 1%; It was concluded that there is a positive relationship between oil prices and BIST100 index at a statistically significant level of 10%. The analysis results for the second model showed that there is no cointegration relationship between the BIST100 index and the consumer confidence index. Finally, within the scope of the study, the direction of causality between the variables was tested by performing the Granger causality test for the first model, which has a cointegration relationship. Accordingly, while one-way causality was detected from gold, oil and BIST100 index to industrial production index, from M2 money supply and foreign exchange to BIST100 index, and from M2 money supply to CPI; Bidirectional causality was found between M2 money supply and interest and foreign exchange, between CPI and BIST100 index, and between interest and foreign exchange.
Keywords: Macroeconomic variables; stock market; investor sentiment; ARDL bounds test; Granger test.